Beneficial Effects of an 8-Week, Very Low Carbohydrate Diet Intervention on Obese Subjects - Gu, Yunjuan (Hindawi Publishing Corporation, 2013)
Aim. To investigate the effects of weight loss during an 8-week very low carbohydrate diet (VLCD) on improvement of metabolic parameters, adipose distribution and body composition, and insulin resistance and sensitivity in Chinese obese subjects. Methods. Fifty-three healthy obese volunteers were given an 8-week VLCD. The outcomes were changes in anthropometry, body composition, metabolic profile, abdominal fat distribution, liver fat percent (LFP), and insulin resistance and sensitivity. Results. A total of 46 (86.8%) obese subjects completed the study. The VLCD caused a weight loss of −8.7 ± 0.6 kg (mean ± standard error (SE), P < 0.0001) combined with a significant improvement of metabolic profile. In both male and female, nonesterified fatty acid (NEFA) significantly decreased (−166.2 ± 47.6 μmol/L, P = 0.001) and β-hydroxybutyric acid (BHA) increased (0.15 ± 0.06 mmol/L, P = 0.004) after eight weeks of VLCD intervention. The significant reductions in subcutaneous fat area (SFA), visceral fat area (VFA), and LFP were −66.5 ± 7.9 cm(2), −35.3 ± 3.9 cm(2), and −16.4 ± 2.4%, respectively (all P values P < 0.0001). HOMA IR and HOMA β significantly decreased while whole body insulin sensitivity index (WBISI) increased (all P values P < 0.001). Conclusion. Eight weeks of VLCD was an effective intervention in obese subjects. These beneficial effects may be associated with enhanced hepatic and whole-body lipolysis and oxidation.